ANALISIS KEMATANGAN EMOSI MAHASISWA DITINJAU DARI MAHASISWA YANG NGEKOS DENGAN MAHASISWA YANG TINGGAL BERSAMA ORANG TUANYA - Annisa Arumaisyah Daulay Daulay; Frizki Shelia Yala Putri; M Haekal Aunilla; Muhammad Ilham Sitompul; Sahrani Simarmata (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
The purpose of this study is to investigate the relationship between emotional development and boarding students' conduct and students who live with their parents. Students from UINSU MEDAN served as the study's subjects. The information was gathered using assessments of behavioral and emotional maturity. Data is examined in terms of product moment. The two variables have a rxy=-0.906 correlation coefficient with a p=0.000 (p0.01) value. This implies that there is a strong inverse relationship between emotional development and these actions. Aggressive conduct can decrease as emotional maturity increases, but it can also increase as emotional immaturity decreases. 82% of people are emotionally mature enough to behave aggressively.